A Strategy for Collaboration Between Educational Institutions and the Field of Practice, Aimed at Profession-Relevant Teacher Education - Hiim, Hilde; Sylte, Ann Lisa (Social Education Research, 2025)
The purpose of this article is to present and discuss a strategy for collaboration between educational institutions and the field of practice, aimed at profession-relevant teacher education. The article is based on the results of a comprehensive action research project on teacher education schools at Oslo Metropolitan University (OsloMet) in Norway. The main goal of the project was to develop a collaboration that could enhance the quality of student teachers’ practical training as well as the professional relevance of teacher education programs. The conceptual framework of the study is grounded in epistemological analyses of what constitutes teachers’ professional competence, based on pragmatic and critical epistemology. The methodological approach is action research and emphasizes practitioner research and dialogue-based action research. The development activities that were carried out were organized around collaboration between the teacher education institution and schools on a 30-credit school-based continuing and further education program for mentor teachers. The results provide examples of how educational institutions, and the field of practice can jointly plan and implement education that focuses on developing teachers’ professional competence through experiential, participatory learning and research. A main principle is that the parties must collaborate to anchor the educational content in ongoing practical experience with professional tasks as a teacher or mentor. The collaboration must also involve the creation of opportunities for teachers and student teachers to develop professional competence by learning to conduct research in their own teaching practice, and to contribute to the development of the school as a learning, participatory organization. The findings also indicate that the development of teacher educators’ competence and organizational learning within teacher education institutions is crucial for achieving profession-relevant teacher education.